Service Integration and Management (SIAM(tm)) Professional Body of Knowledge (BoK) - Agutter, Claire (IT Governance Ltd, 2021)
Service Integration and Management (SIAM(tm)) Professional Body of Knowledge (BoK), Second edition has been updated to reflect changes to the market and is the official guide for the EXIN SIAM(tm) Professional certification. Prepare for your SIAM(tm) Professional exam and understand how SIAM can benefit your organization - pre-order your copy today!